2018
DOI: 10.1002/jnr.24335
|View full text |Cite
|
Sign up to set email alerts
|

Blood–brain barrier disruption and angiogenesis in a rat model for neurocysticercosis

Abstract: Neurocysticercosis (NCC) is a helminth infection affecting the central nervous system caused by the larval stage (cysticercus) of Taenia solium. Since vascular alteration and blood-brain barrier (BBB) disruption contribute to NCC pathology, it is postulated that angiogenesis could contribute to the pathology of this disease. This study used a rat model for NCC and evaluated the expression of two angiogenic factors called vascular endothelial growth factor (VEGF-A) and fibroblast growth factor (FGF2). Also, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
1
13
1
Order By: Relevance
“…This contrasts a previous report by our group which showed angiogenesis in NCC-infected brain slices as well as an increase in VEGF-A protein expression surrounding the cyst [ 10 ]. Even though we did not find significantly increased levels of gene expression associated with angiogenesis in this study, it is evident that in the tissue surrounding the cyst, angiogenesis is present and expected [ 10 , 17 ]. Furthermore, we did not observe a parallel relationship between VEGF-A RNA levels in this study and VEGF-A protein levels reported in our previous study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts a previous report by our group which showed angiogenesis in NCC-infected brain slices as well as an increase in VEGF-A protein expression surrounding the cyst [ 10 ]. Even though we did not find significantly increased levels of gene expression associated with angiogenesis in this study, it is evident that in the tissue surrounding the cyst, angiogenesis is present and expected [ 10 , 17 ]. Furthermore, we did not observe a parallel relationship between VEGF-A RNA levels in this study and VEGF-A protein levels reported in our previous study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our group has shown in the rat model that changes such as blood-brain-barrier disruption, angiogenic factor overexpression, and axonal swellings occur in the presence of viable cysts [ 10 , 11 ]. Most of these changes have been found and reported in the tissue surrounding the cyst.…”
Section: Introductionmentioning
confidence: 99%
“…For example, VEGF-A and its receptors initiate the formation of immature vessels, while Ang1 and other molecules play essential roles in regulating maturation, stabilization, and remodeling of vessels ( Yancopoulos et al, 1998 ). Pro-angiogenetic factors VEGF-A/VEGFR-2 plays a key role in enhancing angiogenesis during the recovery phase after TBI via activating multiple pro-angiogenetic signaling pathways ( Carmen-Orozco et al, 2019 ). Angiopoietin/Tie2 axis mediates neuroprotection and BBB stability in juvenile mice after TBI ( Brickler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…CNS and induce brain damage via BBB breakdown [55][56][57][58][59]. Research on A. cantonensis has also demonstrated that BBB disruption occurs in mice after A. cantonensis infection [60].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%